Genome-wide analysis of chromatin structure changes upon MyoD binding in proliferative myoblasts during the cell cycle. (22nd January 2021) - Wu, Qianmei; Fujii, Takeru; Harada, Akihito; Tomimatsu, Kosuke; Miyawaki-Kuwakado, Atsuko; Fujita, Masatoshi; Maehara, Kazumitsu; Ohkawa, Yasuyuki
Abstract: MyoD, a myogenic differentiation protein, has been studied for its critical role in skeletal muscle differentiation. MyoD-expressing myoblasts have a potency to be differentiated with proliferation of ectopic cells. However, little is known about the effect on chromatin structure of MyoD binding in proliferative myoblasts. In this study, we evaluated the chromatin structure around MyoD-bound genome regions during the cell cycle by chromatin immunoprecipitation sequencing. Genome-wide analysis of histone modifications was performed in proliferative mouse C2C12 myoblasts during three phases (G1, S, G2/M) of the cell cycle. We found that MyoD-bound genome regions had elevated levels of active histone modifications, such as H3K4me1/2/3 and H3K27ac, compared with MyoD-unbound genome regions during the cell cycle. We also demonstrated that the elevated H3K4me2/3 modification level was maintained during the cell cycle, whereas the H3K27ac and H3K4me1 modification levels decreased to the same level as MyoD-unbound genome regions during the later phases. Immunoblot analysis revealed that MyoD abundance was high in the G1 phase then decreased in the S and G2/M phases. Our results suggest that MyoD binding formed selective epigenetic memories with H3K4me2/3 during the cell cycle in addition to myogenic gene induction via active chromatin formation coupled with transcription. Graphical Abstract: